FAKTOR-FAKTOR YANG HUBUNGAN DENGAN GANGGUAN MENSTRUASI PADA COMMUTER (PENGLAJU) Studi Kasus di Kecamatan Karangawen Kabupaten Demak Tahun 2018 - Fahmi, Umi Latifah; Agusyahbana, Farid; Winarni, Sri (Fakultas Kesehatan Masyarakat, 2018)
Menstrual disorders have a certain relationship to the physical and psychological state of women. Commuter trips result in a lack of fitness, low probability of exercise, low physical activity, increased BMI, and stress. Women who become commuters in Karangawen sub-district have 80% menstrual disorders. Objective: This study aims to analyze the relationship of age, perceived stress commuter, physical activity and exercise habits to menstrual disorders on the commuter. Method: This type of research is explanatory research with a cross sectional study approach. The sample in this study uses a portion of the population of women of childbearing age of 100 respondents who commuter. Data analysis was univariate and bivariate using chi square with Î± = 5%. Results: This study showed that most respondents experienced menstrual disorders (69%), the highest percentage of respondents at the age of 19-22 years (56%), (54%) experienced moderate perceived stress, (82%) low activity, (78%) do not exercise. The results showed a significant correlation between age (p-value = 0.041), perceived stress commuter (p-value = 0.005), exercise habits (p-value = 0.000) with menstrual disorders and no physical activity correlation with menstrual disorders (p -value = 0.063). Conclusion: Variable age, perceived stress commuter, exercise habits have a significant correlation to menstrual disorders. While physical activity does not have a significant correlation. It is expected that female commuters can control stress and increase activity by exercising regularly.